THE CORRELATION BETWEEN EXERCISE ACTIVITY, GENETIC BACKGROUND, FAST FOOD CONSUMPTION, AND DYSMENORRHEA - Dewi Mariatus Sholihah (Universitas Airlangga, 2019)
Background: Most women in Indonesia have experienced dysmenorrhea (54.89%). One of the factors that influence dysmenorrhea is low preventive measures carried out by women such as lack of exercise activity, genetic background, and consumption of fast food. Purpose: This study aims to analyze the correlation between exercise activity, genetic background, and fast food consumption and dysmenorrhea. Method: This study was an analytic observational study with a cross-sectional research design. The research population included the students of Public Health Faculty who had menstruated. The samples were 108 respondents chosen by random sampling technique. The variables examined in this study were genetic background, exercise activity, and fast food consumption and the occurrence of dysmenorrhea. Data collection was carried out in February 2019. The research location was at the Faculty of Public Health, Universitas Airlangga, Surabaya. The data were analyzed using univariate and bivariate analysis based on the chi-square test results. Result: The prevalence of dysmenorrhea experienced by students of Public Health Faculty was 65.70%. The test results showed no correlation between exercise activity and dysmenorrhea (p = 0.47), there was a correlation between dysmenorrhea and genetic background (p = 0.01) and there was no correlation between consumption of fast food and dysmenorrhea (p = 0.53). Conclusion: The study shows the there is a correlation between genetic background and dysmenorrhea. On the other hand, there is no correlation between exercise activity and the consumption of fast food with the occurrence of dysmenorrhea.